2021
DOI: 10.1002/ajp.23257
|View full text |Cite
|
Sign up to set email alerts
|

Topographic distribution of the EEG ad hoc broad bands during sleep and wakefulness in the spider monkey (Ateles Geoffroyi)

Abstract: There is evidence that research on sleep among New World monkeys may provide important knowledge related to the evolution of sleep more broadly in the primate order. Digital electroencephalographic (EEG) analyses provide essential knowledge on sleep in the spider monkey. Recently, specific EEG bands related to sleep in these animals have been obtained using principal component analysis, but the exact spatio-temporal distribution of these EEG bands in this species has not yet been analyzed. This study determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In primates, specifically in rhesus macaques ( Macaca mulatta ), Bimbi et al (2018) reported that during the execution and observation of tasks, EEG activity in the ventral premotor area was associated with changes in the beta band of the central electrodes. Moreover, during REM sleep in spider monkeys, Hernández‐Arteaga et al (2021) found a higher correlation of the alpha band between the F3 and O1–O2 derivations, suggesting that this higher synchronization could represent an arousal state during sleep. In fact, distinct degrees of synchronization between frontal and posterior cortical areas have been reported in humans while solving complex mathematical problems (Molina del Río et al, 2019) or executing working memory tasks (Sarnthein et al, 1998; Sauseng et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In primates, specifically in rhesus macaques ( Macaca mulatta ), Bimbi et al (2018) reported that during the execution and observation of tasks, EEG activity in the ventral premotor area was associated with changes in the beta band of the central electrodes. Moreover, during REM sleep in spider monkeys, Hernández‐Arteaga et al (2021) found a higher correlation of the alpha band between the F3 and O1–O2 derivations, suggesting that this higher synchronization could represent an arousal state during sleep. In fact, distinct degrees of synchronization between frontal and posterior cortical areas have been reported in humans while solving complex mathematical problems (Molina del Río et al, 2019) or executing working memory tasks (Sarnthein et al, 1998; Sauseng et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Given (i) that EEG correlations provide measures of the extent of synchronization between two brain regions, and (ii) that coordinated functionality between areas drives certain processes-some cognitive, others behavioral-we designed a study using data gathered previously by PCA with spider monkeys (Cruz-Aguilar et al, 2020) to identify the spatial distribution of the correlations of ad hoc wide bands during the phases of the sleep-wake cycle. Taking into account previous studies of sleep in this species (Cruz-Aguilar et al, 2015;Cruz-Aguilar et al, 2020;Hernández-Arteaga et al, 2021), and earlier topographic EEG sleep studies (Hernández-Arteaga et al, 2021;Tanaka et al, 1999Tanaka et al, , 2000Werth et al, 1996;Zeitlhofer et al, 1993), we hypothesized that the correlations between different cortical regions will change in response to the novel EEG wide bands as follows, depending on the precise sleep-wake state:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations